Advances in Functional Metal‐Organic Frameworks Based On‐Demand Drug Delivery Systems for Tumor Therapeutics. Issue 8 (8th August 2021) - Nirosha Yalamandala, Bhanu; Shen, Wei‐Ting; Min, Sheng‐Hao; Chiang, Wen‐Hsuan; Chang, Shing‐Jyh; Hu, Shang‐Hsiu
Abstract : Cancer Therapy Metal‐organic‐frameworks (MOFs) possessing various physical‐ or chemical‐responsive properties achieve a precise on‐demand drug release and energy generation for cancer therapy. In article number 2100014, Shang‐Hsiu Hu and co‐workers summarize various MOF‐based stimuli‐responsive systems, including those displaying a single stimulus or multiple stimuli, which enable the controlled release of therapeutic agents upon triggering by exogenous stimuli, endogenous stimuli, and redox stimuli.